Roasted soybean supplements for finishing beef cattle on Brachiaria brizantha pasture - de Oliveira, André Alves [UNESP]; Tilemahos Zervoudakis, Joanis; Hatamoto-Zervoudakis, Luciana Keiko; da Silva Cabral, Luciano; da Silva-Marques, Renata Pereira; Koscheck, Jeferson Fabiano Werner [UNESP]; Guedes de Carvalho, Daniel Marino; Benatti, João Marcos Beltrame [UNESP]; Alonso, Marcella Katherine [UNESP] (Springer Nature, 2015)
Two experiments were conducted to evaluate the inclusion of 0, 14, 27.5 and 41 g/kg roasted soybean (RSB) in protein-energy supplements for the finishing of beef cattle on pastures of Brachiaria brizantha cv. Marandu in the rainy period. In experiment 1, for the evaluation of the nutritional parameters, five rumen-cannulated steers with an initial average body weight of 474.5 kg were utilised. In experiment 2, for the evaluation of performance, 25 intact male zebu cattle with an initial average body weight of 418 kg were utilised. Supply of RSB led to an increase in the intake of crude protein and non-fibre carbohydrates (P < 0.05). The concentrations of rumen ammonia nitrogen increased significantly (P < 0.05) 4 h after supplementation. The animals that received protein-energy supplements had superior (52 %) average daily gain in relation to those receiving mineral mixture. The supply of protein-energy supplements formulated with roasted soybean provided an increase in average daily weight gain and an improvement in the nutritional parameters of finishing beef cattle on pasture in the rainy period.
Keywords: Alternative ingredients; Cattle; Grazing; Intake; Nellore; Rumen